PAST PERCEPTION OF MALAY-MUSLIM IDENTITY IN THE DEEP SOUTH OF THAILAND: AN ANALYTICAL STUDY OF PATANI HISTORY LITERATURE - Aini, Tri Hermawan (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2024)
This study investigates the past perceptions of Malay-Muslim identity in Thailand's Deep South, with a focus on the historical narratives found in Hikayat Patani and Sejarah Kerajaan Melayu Patani. These texts show how the region's identity was shaped by Islamic heritage, cultural traditions, and resistance to external dominance, especially during Patani's annexation by the Siamese kingdom in the late 18th and early 19th centuries. The analysis focuses on the enduring themes of cultural preservation and resistance, which are still relevant in today's contexts as the Malay-Muslim community faces challenges from state integration, globalization, and modern education. By examining how historical memory and contemporary identity discourses interact, this study highlights the significance of historical narratives in forming collective identity and resistance. The results demonstrate how resilient the Malay-Muslim community has been in maintaining its religious and cultural traditions while adjusting to contemporary sociopolitical conditions. By shedding light on the evolving process of identity formation in the face of ongoing marginalization, this study advances our knowledge of the historical and cultural dynamics of the area.